Endothelial Dysfunction Correlates with Liver Fibrosis in Chronic HCV Infection. (27th April 2015) - Barone, Michele; Viggiani, Maria Teresa; Amoruso, Annabianca; Schiraldi, Serafina; Zito, Annapaola; Devito, Fiorella; Cortese, Francesca; Gesualdo, Michele; Brunetti, Natale; Di Leo, Alfredo; Scicchitano, Pietro; Ciccone, Marco Matteo
Abstract : Background . Hepatitis C virus (HCV) infection can exert proatherogenic activities due to its direct action on vessel walls and/or via the chronic inflammatory process involving the liver. Aims . To clarify the role of HCV in atherosclerosis development in monoinfected HCV patients at different degrees of liver fibrosis and with no risk factors for coronary artery disease. Methods . Forty-five patients were included. Clinical, serological, and anthropometric parameters, liver fibrosis (transient liver elastometry (fibroscan) and aspartate aminotransferase to platelet ratio index (APRI)), carotid intima-media thickness (c-IMT), and brachial artery flow-mediated vasodilatation (FMD) were assessed. Patients were divided into 3 tertiles according to fibroscan values. Results . Patients in the third tertile (fibroscan value >11.5 KPa) showed FMD values were significantly lower than second and first tertiles (4.7 ± 1.7 % versus 7.1 ± 2.8 %, p = 0.03 ). FMD values were inversely related to liver elastomeric values. c-IMT values were normal. The risk for endothelial dysfunction development in the third tertile (p = 0.02 ) was 6.9 higher than the first tertile. A fibroscan value >11.5 KPa had a positive predictive power equal to 79% for endothelial dysfunction. Conclusions . HCV advanced liver fibrosis promotes atherosclerosis by inducing endothelial dysfunction independently of common cardiovascular risk factors.